1964
DOI: 10.1080/14786436408222962
|View full text |Cite
|
Sign up to set email alerts
|

The phase diagram of the aluminium-molybdenum system

Abstract: Some changes to the aluminium-rich end of the AI-Mo phase diagram are proposed. The results of several workers indicate that two new phases (MoAI, and MoAI,) have to be introduced and that one phase (MOM,) should be omitted from the existing diagram.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Walford [40] presented an evaluation of the partial AleMo diagram from 0 to 30 at.%Mo. Some aspects of the evaluations are inconsistent with each other and with the literature.…”
Section: Review Of the Alemo Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Walford [40] presented an evaluation of the partial AleMo diagram from 0 to 30 at.%Mo. Some aspects of the evaluations are inconsistent with each other and with the literature.…”
Section: Review Of the Alemo Systemmentioning
confidence: 99%
“…Some aspects of the evaluations are inconsistent with each other and with the literature. Walford [40] modified the partial AleMo phase diagram of Sperner [22] by changing the stoichiometry of the Al 3 Mo phase to Al 8 Mo 3 in accordance with the recommendation of Forsyth and Gran [30], and added the Al 4 Mo phase as detected by Pötzschke and Schubert [24]. Walford [40] also modified the composition of the Al 7 Mo phase, which was found by Clare [23] in slow cooled melts of Al-rich alloys, to Al 6 Mo.…”
Section: Review Of the Alemo Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10][11][12][13][14][15][16] Yamaguchi and Simizu [8] measured the Al-rich liquidus compositions up to 1273 K. Roentgen and Koch, [7] Mondolfo [9] and Vigdorovich et al [14] determined the solid solubility of Mo in fcc (Al). Based on the above experimental data, Walford [17] reviewed the Al-rich region of the Al-Mo system, and concluded that there were five intermediate phases, Al 12 Mo, Al 6 Mo, Al 5 Mo, Al 4 Mo and Al 8 Mo 3 .…”
Section: Al-mo Systemmentioning
confidence: 99%
“…In addition, Ham, [10] Rexer [22] and Shilo and Franzen [23] determined the solubility of Al in bcc(Mo). Based on the assessed result of Walford [17] and the above experimental data (except for Shilo and Franzen [23] and Malinovskii [26] ), Brewer and Lamoreaux [27] reviewed the Al-Mo phase diagram again. They included three solution phases (liquid, bcc (Mo) and fcc (Al)) and ten intermetallic phases: Al 12 Mo, Al 6 Mo, Al 5 Recently, Schuster and Ipser [28] reinvestigated the partial phase diagram between Al and Al 8 Mo 3 , and found ten intermetallic compounds, Al 12 [29] confirmed the phases and phase equilibria reported by Schuster and Ipser [28] with the exception of the phases Al 3+x Mo 1-x (h) and Al 5 Mo(h¢) and determined the homogeneity ranges of the Al-rich intermetallic compounds.…”
Section: Al-mo Systemmentioning
confidence: 99%